Supramolecular assemblies of configuration inorganic semiconductor/oligomer. - Grygorchak, I.I.; Matulka, D.V.; Ivashchyshyn, F.O.; Zaichenko, O.S.; Mitina, N.Ye.; Moskvin, M.M. (Физическая инженерия поверхности, 2012)
The possibility of formation of such supramolecular complexes as inorganic semiconductor/oligomer with use of intercalation technologies is presented in this work. Lamellar semiconductors gallium selenide and indium selenide were objects of research. These compounds were used as the body of host. Molecules of оligomer oligo-dimethylamino-methacrylate were used as guest component. The results of research are represented with using the method of impedance spectroscopy.